2000
DOI: 10.1177/1358836x0000500308
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of abdominal aortic aneurysm

Abstract: Abstract:Abdominal aortic aneurysms (AAA) are increasingly common in the aging population. While the etiology of abdominal aortic aneurysms is unknown, there is growing evidence that suggests an immune response. The majority of AAA are asymptomatic and when treated are standard open surgical procedures. The overall mortality rate is 5% or less. The current recommendations for the treatment of aneurysms are based on diameter: diameters exceeding 5 cm in good-risk younger patients should be treated. Aortic aneur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
1
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 57 publications
0
2
1
1
Order By: Relevance
“…[22][23][24][25] According to the literature, depending on the size of the cycles with classic elective AAA repairs, mortality ranges from 1.8 to 5% 26 to even 9.6%. [27][28][29][30] In our study, we have found nonsignificant differences in 30-day mortality (0 vs. 1, p ¼ ns). We may assume that we were actually underpowered to estimate the differences in such rare outcome.…”
Section: Discussioncontrasting
confidence: 62%
“…[22][23][24][25] According to the literature, depending on the size of the cycles with classic elective AAA repairs, mortality ranges from 1.8 to 5% 26 to even 9.6%. [27][28][29][30] In our study, we have found nonsignificant differences in 30-day mortality (0 vs. 1, p ¼ ns). We may assume that we were actually underpowered to estimate the differences in such rare outcome.…”
Section: Discussioncontrasting
confidence: 62%
“…AAA is a very malignant disease characterized by a high incidence of mortality (70%) after rupture. [ 9 ] A sudden severe pain may indicate peritoneal or retroperitoneal rupture. A growing tumor could result in compression of adjacent organs such as duodenum, the proximal jejunum and ureter, which was observed in our patient who developed hydronephrosis due to an oppression.…”
Section: Discussionmentioning
confidence: 99%
“…An aneurysm is the local dilation of the lumen of a vessel by 50% compared to the proximal, unaffected segment. In practice, the abdominal aortic aneurysm is diagnosed when its diameter is at least 30 mm, measured from the internal to external vessel outline (1)(2)(3)(4)(5)(6)(7). The normal diameter of aorta in the subrenal segment is 1.66-2.16 cm in women and 1.99-2.39 in men (8,9).…”
Section: Introductionmentioning
confidence: 99%